2020
DOI: 10.1111/ejn.14746
|View full text |Cite
|
Sign up to set email alerts
|

In vivo electrophysiological validation of DREADD‐based modulation of pallidal neurons in the non‐human primate

Abstract: Designer receptors exclusively activated by designer drugs (DREADDs) are widely used in rodents to manipulate neuronal activity and establish causal links between structure and function. Their utilization in non-human primates (NHPs) is, however, limited and their efficacy still debated. Here, we recorded and examined the neuronal activity in the hM4Di DREADD-transduced and hM4Di DREADD-free GPe of two anesthetized animals following local intra-GPe microinjection of clozapine-N-oxide (CNO). Our results reveale… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
(105 reference statements)
2
11
0
Order By: Relevance
“…Finally, the duration of effects is much greater than those of clonidine (>2 h; vs. ∼1 h). As Nagai et al (2020) reported, a single dose of DCZ (0.1 mg/kg) induces a reliable effect over more than 2 h. A similar timing was reported for CNO-mediated DREADD inhibition of the striatum [ 29 ]. Here, the effects of the drug were stable over the entire duration of the recording sessions (>1 h), but they had completely disappeared after 24 h, which would enable us to conduct daily sessions as usually performed with laboratory monkey experiments.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Finally, the duration of effects is much greater than those of clonidine (>2 h; vs. ∼1 h). As Nagai et al (2020) reported, a single dose of DCZ (0.1 mg/kg) induces a reliable effect over more than 2 h. A similar timing was reported for CNO-mediated DREADD inhibition of the striatum [ 29 ]. Here, the effects of the drug were stable over the entire duration of the recording sessions (>1 h), but they had completely disappeared after 24 h, which would enable us to conduct daily sessions as usually performed with laboratory monkey experiments.…”
Section: Discussionsupporting
confidence: 57%
“…In recent years, chemogenetics has become a very efficient method to reversibly manipulate large populations of neurons in monkeys [ 20 , 29 , 30 , 31 , 32 ]. Here, we demonstrate that the method can be used to target specific populations of neurons over a relatively long time (several hours), with an efficacy of inactivation falling within the expected range, i.e., sufficient to obtain functional effect but limited enough on vigilance to allow the monkeys to perform standard laboratory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the functional role of the STN in motor control, in the present study, we utilized the Designer Receptors Exclusively Activated by a Designer Drug (DREADD) technology to manipulate the neural activity in the STN of macaque monkeys. Although DREADDs have been utilized widely in rodents, application in sub-human primates is rather limited and only one electrophysiologic evaluation at the single-neuron level 28 is reported. Here, we showed that administration of DREADD ligands moderately reduced STN activity, which was sufficient to induce abnormal involuntary movements and extend the movement time.…”
Section: Introductionmentioning
confidence: 99%
“…Combining neuromodulation including electrical stimulation or muscimol injection with the monkey fMRI has shown to be a powerful approach for causally linking neural activity to behavior or testing neural coupling across brain regions (Bogadhi et al, 2019;Ekstrom et al, 2008;Klink et al, 2021;Miyamoto et al, 2017;Moeller et al, 2008;Rocchi et al, 2021;Schmid et al, 2010;Tolias et al, 2005;Van Dromme et al, 2016;Verhagen et al, 2019;Wilke et al, 2012;Xu et al, 2019;Yang et al, 2018). Compared with conventional neuromodulation approaches, genetic intervention has certain advantages, including anatomical and/or cell-type specificity of the manipulation target, which has been applied to non-human primates to change behavior and/or local neuronal activity at the manipulated region (Deffains et al, 2021;El-Shamayleh and Horwitz, 2019;Eldridge et al, 2016;Nagai et al, 2016;Raper et al, 2019;Upright et al, 2018). Given that the impact of focal neuromodulation is not necessarily localized to the manipulation target but extends to anatomically and/or functionally connected remote regions, induced behavioral changes would reflect the altered network operation (Bergmann and Hartwigsen, 2021;Carrera and Tononi, 2014).…”
Section: Introductionmentioning
confidence: 99%